Perception Threshold Variations of Pain Area with Herpetic Ophthalmic Neuralgia - Xǔ Gang; Zhou Chao-Sheng; Cheng Chao (Journal of Ophthalmic Science, 2018)
Background: To measure the affected subepidermal nerve sensation with a combination of current perception threshold (CPT) and Semmes-Weinstein monofilament (SWM) testing under pain areas with herpetic ophthalmic neuralgia (HON). Methods: One hundred fifty-five subjects with HON and 30 age-matched volunteers were recruited for the study. Results: The combined SWM and CPT testing yielded significantly abnormal responses at the painful sites for the patients with HON compared to those responses of the normal controls (p< 0.05). The SWM and CPT tests were able to distinguish local hypoesthesia of pain areas when the cut-off values were 0.135g, 53 (5Hz), 66 (250Hz) and 199 (2,000Hz). The ratio of the painful site to the mirror site indicated there were significant differences in the CPT ratio at 250Hz and 2,000Hz among different pain characteristic groups. Post hoc tests showed significant differences in CPT250Hz between itching and lancinating pain (p=0.006), itching and allodynia (p=0.002), and burning pain and allodynia (p=0.042). There were significant differences in CPT2000Hz between deep pain and allodynia (p=0.001) and itching and allodynia (p=0.014). Conclusion: CPT and SWM testing can probably be used as semi-quantitative indicators to represent the neural function at the local skin of pain area with HON.
Keywords: herpetic ophthalmicus neuralgia — subepidermal nerve fibers — current perception threshold — semmes-weinstein monofilament — noninvasive